COVID-19 inactivated and non-replicating viral vector vaccines induce regulatory training phenotype in human monocytes under epigenetic control - Antunes, Mateus da Silva Matias; Sugiyama, Fabricia Heloisa Cavicchioli; Gravina, Humberto Doriguetto; Castro, Ricardo Cardoso; Mercado, Francisco Javier Romero; Lima, Julia Oliveira de; Fontanari, Caroline; Frantz, Fabiani Gai (Frontiers in Cellular and Infection Microbiology, 2023)
Background Trained immunity is the enhanced innate immune response resulting from exposure to pathogens or vaccines against an unrelated pathogen stimulus. Certain vaccines induce a memory like response in monocytes and NK cells, leading to modulation in cytokine production, metabolic changes, and modifications in histone patterns. Here, we hypothesized that vaccination against SARS-CoV-2 could induce the training of monocytes in addition to stimulating the adaptive immune response. Methods Therefore, we aimed to investigate the immunophenotyping, cytokine and metabolic profile of monocytes from individuals who were completely immunized with two doses of inactivated COVID-19 vaccine or non-replicating viral vector vaccine. Subsequently, we investigated the epigenetic mechanisms underlying monocyte immune training. As a model of inflammatorychallenge, to understand if the monocytes were trained by vaccination and how they were trained, cells were stimulated in vitro with the endotoxin LPS, an unrelated stimulus that would provoke the effects of training. Results When challenged in vitro, monocytes from vaccinated individuals produced less TNF-α and those who received inactivated vaccine produced less IL-6, whereas vaccination with non-replicating viral vector vaccine induced more IL-10. Inactivated vaccine increased classical monocyte frequency, and both groups showed higher CD163 expression, a hallmark of trained immunity. We observed increased expression of genes involved in glycolysis and reduced IRG1 expression in vaccinated subjects, a gene associated with the tolerance phenotype in monocytes. We observed that both vaccines reduced the chromatin accessibility of genes associated with the inflammatory response, the inactivated COVID-19 vaccine trained monocytes to a regulatory phenotype mediated by histone modifications in the IL6 and IL10 genes, while the non-replicating viral vector COVID-19 vaccine trained monocytes to a regulatory phenotype, mediated by histone modifications in the IL6, IL10, TNF, and CCL2 genes. Conclusions Our findings support the recognized importance of adopting vaccination against SARS CoV-2, which has been shown to be effective in enhancing the adaptive immune response against the virus and reducing mortality and morbidity rates. Here, we provide evidence that vaccination also modulates the innate immune response by controlling the detrimental inflammatory response to unrelated pathogen stimulation.